Performance enhancement and size reduction of near-eye display - Cheng, Qijia (Nanyang Technological University, 2020)
Near-eye display (NED) paved its way in a variety of applications of modern virtual reality (VR). However, current NEDs have lots of limitations, which lead to compromised user experience and strongly limit their potential in real-world scenarios. Two of the most noticeable features that demanding improvements are resolution and size. On the one hand, applications of modern VR devices introduce more detailed textures and increased field-of-view (FoV), altogether create excessive demand for resolution. On the other hand, more mobile application scenarios of virtual reality and augmented reality (AR) bring the requirement of size reduction. The trend of developing high-resolution NED with small form-factor is with no doubt. During the last several decades, attempts were made to improve the resolution of NED. However, the utilization of eye-tracking and optical tiling adds a fairly amount of complexity to the NED system, which in turn makes the device even bulkier. Thus, a compact near-eye display device that can deliver excellent image quality is still in great demand by society. In this thesis, theory and methods are demonstrated to improve key performance factors in modern NED, including resolution, depth perception, and size.